2012
DOI: 10.1042/bst20110648
|View full text |Cite
|
Sign up to set email alerts
|

MKP-2: out of the DUSP-bin and back into the limelight

Abstract: The MKPs (mitogen-activated protein kinase phosphatases) are a family of at least ten DUSPs (dual-specificity phosphatases) which function to terminate the activity of the MAPKs (mitogen-activated protein kinases). Several members have already been demonstrated to have distinct roles in immune function, cancer, fetal development and metabolic disorders. One DUSP of renewed interest is the inducible nuclear phosphatase MKP-2, which dephosphorylates both ERK (extracellular-signal-regulated kinase) and JNK (c-Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The best-studied role for DUSPs is in negative-feedback regulation of mitogen-activated kinase (MAPK) signaling cascades (reviewed by Lawan et al, 2012). MAPK phosphatases (MKPs) simultaneously dephosphorylate threonine and tyrosine residues within the MAPK activation loop to attenuate signaling in a wide variety of physiological contexts, including immune function, embryonic development and metabolic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The best-studied role for DUSPs is in negative-feedback regulation of mitogen-activated kinase (MAPK) signaling cascades (reviewed by Lawan et al, 2012). MAPK phosphatases (MKPs) simultaneously dephosphorylate threonine and tyrosine residues within the MAPK activation loop to attenuate signaling in a wide variety of physiological contexts, including immune function, embryonic development and metabolic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests MKP-2 deletion may have effects which regulate other components of the ERK cascade including receptor expression and functional coupling to upstream intermediates. A number of studies including our own have also suggested that MKP-2 can regulate cellular function in a way which is not dependent on the normal predicted effects on ERK and JNK 11 33 34. Indeed, recently MKP-2 has been shown to interact and regulate the cell cycle protein VRK-1 independently of phosphatase activity suggesting multiple cellular effects 35.…”
Section: Discussionmentioning
confidence: 90%
“…MKP-2 (DUSP4) is a type 1 nuclear phosphatase10 specific for ERK and JNK in vitro. As a type 1 DUSP, MKP-2 has been viewed as a surrogate to the prototypic MKP-1 and less extensively examined 11. However, more recent studies have identified distinct roles for MKP-2 in different cellular processes and associated pathologies such as tumour development,12 13 cancer resistance,14 cardiac myopathy,15 infection16 and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These are termed dual-specificity phosphatases (DUSPs), and each member of the DUSP family has a unique set of properties including tissue distribution, subcellular localization, and precise substrate affinity and specificity [96]. For example, MKP-1 targets primarily p38 MAPK contrary to MKP-2 which preferentially dephosphorylates ERK and JNK [9799]. The strength and duration of p38 MAPK activation are often the critical determinant of cellular responses regulated by the action of these phosphatases [100].…”
Section: Targeting P38 Mapk In Pemphigus: Corticosteroids Versus Mmentioning
confidence: 99%